EFFECT OF INTERCROPPING IN SHADING WITH CROTALARIA ON THE INITIAL DEVELOPMENT OF COFFEE TREE - Franco Junior, Kleso Silva; Carvalho Terra, Ana Beatriz; Florentino, Ligiane Aparecida; Carvalho, Julian Silva; Guimarães, Bernardino Cangussu; Silva, Nilton de Oliveira (Coffee Science - ISSN 1984-3909, 2019)
Coffee cultivation in Brazil is still predominantly in full sun. However, the shading technique has gained prominence to increase the sustainability and profitability of production. Coffee intercropping legumes, besides contributing to shading, act as green manure, improving soil characteristics. Thus, in this study the objective was evaluating the shading intercropping effect on the initial development of coffee trees. The experiment was carried out at Sítio Santa Felicidade, municipality of Campestre - Southern Minas Gerais. Four species of the Crotalaria genus were used and one control treatment without any intermediate species, totaling 5 treatments. The planting was carried out in 4 replicates per treatment, in a randomized block system (DBC), with 16 coffee plants per plot. The 10 central plants were used for evaluation. The variables analyzed were: seedling setting (%), plant height (cm), leaf area index (LAI), number of plagiotropic branch internodes and 50 cm from ground level (cm²), temperature (°C) and soil moisture (%). Data were statistically interpreted by variance analysis and comparisons of averages performed by the Scott-Knott test at 5% probability, using the statistical software SISVAR®. It was observed that, except seedling setting (%) wherein there was no statistical difference among treatments, the other parameters showed positive responses in intercropping with crotalaria when compared to the control, showing the beneficial effect of the use of this legume when intercropped with coffee tree.